RARE STRUCTURAL GENETIC VARIATION IN HUMAN PRION DISEASES. Issue 12 (15th November 2016) - Lukic, Ana; Uphill, James; Brown, CA; Beck, Jon; Poulter, Mark; Campbell, Tracey; Adamson, Gary; Hummerich, Holger; Collinge, John; Mead, Simon
Abstract : Prion diseases are a diverse group of neurodegenerative diseases, caused by prion protein misfolding. Aside from the strong genetic risk conferred by multiple variants of the prion protein gene (PRNP), several other risk variants have been suggested. Copy number variants (CNVs) are known to confer risk in several related neuropsychiatric and neurodegenerative conditions. Here, we report the first genome-wide analysis for CNV-associated risk in sCJD (n=1147) and publicly available controls (n=5427). We also investigated UK patients with vCJD (n=114) and elderly women from Papua New Guinea resistant to kuru, who were compared with healthy young Fore population controls (n=395). There were no statistically significant alterations in the burden of CNV duplications or deletions in any disease group or geographic region after correction for multiple testing. Heterozygous deletions of 3' region of the PARK2 gene were found in 3 sCJD patients and no controls (p=0.001, uncorrected). A cell-based prion infection assay did not confirm the role of PARK2 in prion disease susceptibility. These data are consistent with a modest impact of CNVs on risk of late-onset neurologic conditions and suggest that, unlike APP, PRNP duplication is not a causal high-risk mutation.